Preparation and application of porous carbon sphere composites modified with Ni2SeS alloy nanorods as a novel hydrogen evolution reaction catalyst

By combining hydrothermal method and vapor deposition, a porous carbon sphere composite material modified with Ni2SeS alloy nanorods was prepared, which solved the problems of high cost and limited reserves of platinum-based catalysts in the prior art, and achieved a hydrogen evolution reaction catalyst with low cost and good stability, with excellent electrochemical hydrogen evolution performance and broad application prospects.

CN113279012BActive Publication Date: 2025-04-04TONGJI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010098308.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-02-18
Publication Date
2025-04-04
Estimated Expiration
2040-02-18

AI Technical Summary

Technical Problem

In the prior art, platinum-based catalysts have high cost and limited reserves, making it difficult to develop a non-precious metal carbon-based nanocomposite structure for hydrogen evolution reactions with low cost and good stability.

Method used

By combining hydrothermal method with vapor deposition, a porous carbon sphere composite material modified with Ni2SeS alloy nanorods was prepared as a hydrogen evolution reaction catalyst using nickel salt and selenium powder as raw materials.

Benefits of technology

This catalyst has excellent electrochemical hydrogen evolution performance, low cost and good stability, suitable for medium-scale industrial production, and has important application prospects in green energy fields such as electrolytic hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113279012B_ABST
    Figure CN113279012B_ABST
Patent Text Reader

Abstract

A hydrogen evolution reaction catalyst, comprising Ni2SeS and porous carbon spheres, is a porous carbon composite material modified by alloy nanorods Ni2SeS, and a preparation method thereof comprises the following steps: (1) preparing a NiSe2 / PCS composite material by a hydrothermal synthesis method; (2) preparing a Ni2SeS / PCS composite material by a chemical vapor deposition method. The hydrogen evolution reaction catalyst is applied to electrocatalytic hydrogen evolution. The present invention adopts nickel salt as a nickel source and selenium powder as a selenium source, and successfully prepares a binary metal sulfide-carbon-based composite material by a method combining a hydrothermal method with vapor deposition. The hydrogen evolution reaction catalyst has excellent electrochemical hydrogen evolution properties. The process of the present invention is simple, the preparation conditions are universal, the product morphology is stable, the purity is high, and the product processing is convenient and concise, and is suitable for medium-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a hydrogen evolution reaction catalyst, a preparation method and application thereof. Background Art

[0002] In recent years, renewable energy has gained increasing attention as an alternative to fossil fuels. Hydrogen, with its high energy density and eco-friendliness, is considered an ideal energy carrier for achieving sustainable economic development. Water electrolysis is a viable method for producing high-purity, large quantities of hydrogen. However, the presence of a cathode overpotential requires a significant amount of additional electrical energy, limiting its practical application.

[0003] Platinum (Pt), the most commonly used electrocatalyst in the hydrogen evolution reaction (HER), exhibits a very high exchange current density (J0) and a low Tafel slope. However, Pt-based noble metal catalysts are expensive and have limited reserves. Therefore, it is imperative to develop and construct non-noble metal carbon-based nanocomposite structures with high catalytic activity and good stability, and to prepare binary or even multi-element alloy nanocatalytic systems to reduce the cost of HER catalysts and develop HER catalysts with practical application value.

[0004] A large number of research works have confirmed that many earth-abundant elements are expected to replace platinum (Pt) as efficient hydrogen evolution catalysts. In recent years, transition metal dichalcogenides MX2 (where M = Fe, Co, Ni, X = S, Se or Te) have attracted widespread attention due to their low cost and electrochemical stability in acidic media. Compared with traditional single metal sulfides and selenides, the introduction of selenium into metal sulfides can adjust the d-band electronic structure of the metal, causing its electronic energy state to shift towards the Fermi level, thereby regulating the H ads The adsorption free energy of the catalyst is low, thus it has better electrocatalytic hydrogen evolution performance than sulfides and selenides. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a hydrogen evolution reaction catalyst, its preparation method and application, using common nickel salt as a nickel source and Se powder as a selenium source to synthesize Ni2SeS alloy nanorod-modified porous carbon sphere (PCS) composite materials by a hydrothermal method.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A hydrogen evolution reaction catalyst comprises Ni2SeS and porous carbon spheres.

[0008] Furthermore, the hydrogen evolution reaction catalyst is a Ni2SeS modified porous carbon sphere composite material.

[0009] The preparation method of the hydrogen evolution reaction catalyst comprises the following steps:

[0010] (1) Preparation of NiSe2 / PCS composites by hydrothermal synthesis;

[0011] (2) Prepare Ni2SeS / PCS composite materials by chemical vapor deposition.

[0012] Furthermore, the preparation method of the NiSe2 / PCS composite material includes:

[0013] (1) Weighing nickel salt, dissolving it in a solvent, and adding it to a reactor;

[0014] (2) Weigh the porous carbon spheres and add them into the reactor, and disperse them evenly by ultrasonication;

[0015] (3) Add Se powder to the reactor, then inject hydrazine hydrate solution and stir;

[0016] (4) heating the reactor and keeping it warm;

[0017] (5) The reaction system was cooled to room temperature, the product in the reactor was centrifuged, washed alternately with anhydrous ethanol and deionized water three times, and vacuum dried to obtain a NiSe2 / PCS composite material.

[0018] In the preparation method of the NiSe2 / PCS composite material, the solvent in step (1) is deionized water.

[0019] In the preparation method of the NiSe2 / PCS composite material, the purity of the nickel salt in step (1) is not less than chemical purity.

[0020] In the preparation method of the NiSe2 / PCS composite material, in step (2), the concentration of the porous carbon spheres (PCS) dissolved in deionized water is 0.5-1 mg / mL.

[0021] In the preparation method of the NiSe2 / PCS composite material, the purity of the Se powder in step (3) is not less than chemical purity.

[0022] In the preparation method of the NiSe2 / PCS composite material, the mass ratio of the nickel salt in step (1) to the porous carbon spheres (PCS) in step (2) is (1.5-6):1.

[0023] In the preparation method of the NiSe2 / PCS composite material, the mass ratio of the Se powder in step (3) to the nickel salt in step (1) is 2:1.

[0024] In the preparation method of the NiSe2 / PCS composite material, the mass concentration of the hydrazine hydrate solution in step (3) is 60%-80%.

[0025] In the preparation method of the NiSe2 / PCS composite material, the volume of the hydrazine hydrate solution in step (3) is 1 mL-2 mL.

[0026] In the preparation method of the NiSe2 / PCS composite material, the heating rate in step (4) is 2°C / min-5°C / min.

[0027] In the preparation method of the NiSe2 / PCS composite material, the holding temperature in step (4) is 180°C-200°C.

[0028] In the preparation method of the NiSe2 / PCS composite material, the holding time in step (4) is 18h-24h.

[0029] In the preparation method of the NiSe2 / PCS composite material, the vacuum drying time in step (5) is 4h-10h.

[0030] In the preparation method of the NiSe2 / PCS composite material, the vacuum drying temperature in step (5) is 60°C-70°C.

[0031] In addition, the preparation of the Ni2SeS / PCS composite material includes:

[0032] (1) Weigh NiSe2 / PCS and spread it evenly in a corundum boat;

[0033] (2) Place the porcelain boat in the center of the quartz tube in the CVD tube furnace and place the sulfur powder at the upwind side of the quartz tube;

[0034] (3) introducing N2 gas flow as protective gas flow;

[0035] (4) Under the protection of N2 atmosphere, heat up and keep warm;

[0036] (5) The reaction system was cooled to room temperature, and the product was collected by vacuum drying to obtain a Ni2SeS / PCS composite material.

[0037] In the preparation method of the Ni2SeS / PCS composite material, the flow rate of the N2 carrier gas protection gas flow in step (3) is 0.5L / min-0.8L / min.

[0038] In the preparation method of the Ni2SeS / PCS composite material, the heating rate in step (4) is divided into two stages; the first stage is 5°C / min-10°C / min; the second stage is 2°C / min-5°C / min.

[0039] In the preparation method of the Ni2SeS / PCS composite material, the holding temperature in step (4) is 450°C-500°C.

[0040] In the preparation method of the Ni2SeS / PCS composite material, the holding time in step (4) is 1h-2h.

[0041] In the preparation method of the Ni2SeS / PCS composite material, the mass ratio of NiSe2 / PCS in step (1) to the sulfur powder in step (2) is 1:5-1:20.

[0042] The Ni2SeS alloy nanorod-modified porous carbon sphere composite material prepared according to the above preparation method is made of the following components: Ni2SeS and porous carbon spheres (PCS).

[0043] The application of the porous carbon sphere composite material modified with Ni2SeS alloy nanorods prepared according to the above preparation method in electrocatalytic hydrogen evolution.

[0044] Due to the adoption of the above solution, the beneficial effects of the present invention are:

[0045] 1. The method of combining hydrothermal method with vapor deposition in the present invention has certain universality for preparing binary or even multi-component metal sulfides.

[0046] 2. Simple inorganic salts are used as reactants, the raw materials are abundant in reserves and the industrial cost is low.

[0047] 3. The product prepared according to this method has good electrochemical hydrogen evolution performance and can be used as a high-performance electrocatalytic hydrogen evolution material with broad development prospects and application space.

[0048] 4. The process of the present invention is simple, the preparation conditions are mild, the product morphology is stable, the purity is high, and the product processing is convenient and simple, which is suitable for medium-scale industrial production.

[0049] 5. The method of the present invention loads multi-metal sulfides on carbon-based materials, which not only increases the conductivity of the metal sulfides, but also greatly improves the cyclic stability of the composite material. It will have important application prospects in green energy fields such as water electrolysis to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The following are SEM photos of the product obtained by PCS in Example 1 at magnifications of 1 μm, 2 μm, and 500 μm, wherein: Figure A is an SEM photo of the product obtained by PCS in Example 1 at a magnification of 1 μm;

[0051] Figure B is a SEM photo of the product obtained from PCS in Example 1 at a magnification of 2 μm;

[0052] Figure C is a SEM photograph of the product obtained from PCS in Example 1 at a magnification of 500m.

[0053] Figure 2 The SEM photos, XRD patterns and EDS patterns of the NiSe2 / PCS product in Example 1 are shown, wherein: Figure A is an SEM photo of the NiSe2 / PCS product in Example 1 obtained at a magnification of 1 μm;

[0054] Figure B is a SEM photo of the NiSe2 / PCS product obtained in Example 1 at a magnification of 200 nm;

[0055] Figure C is the XRD pattern of NiSe2 / PCS in Example 1;

[0056] Figure D is the EDS spectrum of NiSe2 / PCS in Example 1.

[0057] Figure 3 The following are the SEM photos, TEM photos, XRD patterns and EDS patterns of the Ni2SeS / PCS product in Example 1, wherein:

[0058] Figure A is a SEM photograph of the product of Ni2SeS / PCS obtained in Example 1 at a magnification of 500 μm;

[0059] Figure B is a SEM photograph of the product of Ni2SeS / PCS obtained at a magnification of 200 m in Example 1;

[0060] Figure C is a TEM image of the product of Ni2SeS / PCS obtained at a magnification of 200 m in Example 1;

[0061] Figure D is a TEM image of the product of Ni2SeS / PCS obtained in Example 1 at a magnification of 100 m;

[0062] Figure E is the XRD pattern of Ni2SeS / PCS in Example 1;

[0063] Figure F is the EDS spectrum of Ni2SeS / PCS in Example 1. DETAILED DESCRIPTION

[0064] The present invention will be further described in detail below with reference to the embodiments shown in the accompanying drawings.

[0065] Example 1

[0066] (1) Preparation of NiSe2 / PCS

[0067] First, weigh 120 mg of nickel nitrate hexahydrate and dissolve it in 30 mL of deionized water. Stir at room temperature for 5 minutes. Use a pipette to transfer 20 mL of the solution to a polytetrafluoroethylene reactor.

[0068] In the second step, 20.0 mg of porous carbon spheres were accurately weighed and added to the above reactor, and ultrasonically dispersed uniformly;

[0069] In the third step, 43.58 mg of Se powder was added to the above reaction kettle at room temperature, and then 2 ml of 80% hydrazine hydrate solution was injected and stirred for 30 minutes to mix evenly. The solution was observed to change from green to purple suspension;

[0070] The fourth step was to place the reactor in an electric constant temperature blast drying oven, and heat the temperature from room temperature to 180°C at a rate of 2°C / min and keep the temperature for 24 hours.

[0071] The fifth step is to wait until the reaction system cools down to room temperature naturally, transfer the product in the reactor into a centrifuge tube, centrifuge and wash it alternately with anhydrous ethanol and deionized water for 3 times, then place the product in a vacuum drying oven at 60°C and dry it for 4 hours, take out the product and seal it for storage.

[0072] (2) Preparation of Ni2SeS / PCS

[0073] Step 1: Weigh 40 mg of the NiSe2 / PCS prepared above and spread it evenly in a 1 cm x 4 cm corundum boat;

[0074] Step 2: Place the porcelain boat in the center of the quartz tube in the CVD tube furnace and place 0.2g of sulfur powder at the upwind side of the quartz tube;

[0075] Step 3: Before the reaction starts, a certain amount of N2 gas is introduced and the flow rate is maintained at 0.5 L / min;

[0076] Step 4: Under N2 atmosphere, the temperature was rapidly increased from room temperature to 200°C at a heating rate of 10°C / min, and then slowly increased to 450°C at a heating rate of 2°C / min and kept at this temperature for 1 hour.

[0077] Step 5: Wait until the reaction system cools down to room temperature naturally, and transfer the product in the porcelain boat to a test tube for further characterization and testing.

[0078] As shown in the figure:

[0079] Figure 1 (AC) are emission scanning electron microscope (SEM) images of porous carbon spheres obtained at different magnifications in Example 1.

[0080] Figure 2 (A, B) show the SEM images of the prepared NiSe2 / PCS. It can be seen that the prepared NiSe2 particles are tightly attached to the porous carbon spheres, filling the entire inner surface of the porous carbon spheres and the porous carbon sphere skeleton. X-ray diffraction analysis (XRD) of NiSe2 Figure 2(C) It can be observed at 29.9°, 33.5°, 36.9°, 50.7°, 55.5° and 57.8°

[0081] The diffraction peaks of NiSe2 (200), (210), (211), (311), (023) and (321) crystal planes appear at the locations corresponding to the PDF#65-1843 card of NiSe2. Figure 2 (D) Characterization shows that the atomic ratio of Se:Ni is approximately 2:1, further demonstrating the successful loading of NiSe2 on porous carbon spheres PCS.

[0082] Figure 3 (A, B) show the SEM images of Ni2SeS / PCS at different magnifications in Example 1. It can be seen that Ni2SeS is evenly attached to the inner and outer surfaces of the porous carbon spheres (PCS). Figure 3 (C, D) show the N at different magnifications in Example 1 i2 From the TEM image of SeS / PCS, it can be seen that the diameter of Ni2SeS particles is about 100nm, which is larger than that of NiSe2 particles, and they are arranged tightly and orderly. Figure 3 (E) is the XRD pattern of the prepared Ni2SeS / PCS. Diffraction peaks corresponding to the (101), (102), (110) and (112) crystal planes of Ni2SeS can be observed at 33.5°, 44.8°, 51.3° and 62.7°, respectively, corresponding to the PDF#65-4017 card of Ni2SeS. Figure 3 (F) is the EDS image of the prepared Ni2SeS / PCS.

[0083] Through this characterization, it was demonstrated that the ratio of Ni:Se:S in the prepared Ni2SeS / PCS was approximately 2:1:1.

[0084] Example 2

[0085] Adjust the ratio of nickel salt and carbon spheres in the preparation of NiSe2 / PCS.

[0086] (1) Preparation of NiSe2 / PCS

[0087] First, weigh 120 mg of nickel nitrate hexahydrate and dissolve it in 30 mL of deionized water. Stir at room temperature for 5 minutes. Use a pipette to transfer 20 mL of the solution to a polytetrafluoroethylene reactor.

[0088] In the second step, 80.0 mg, 40.0 mg, and 20.0 mg of porous carbon spheres were accurately weighed and added to the above reactor, and ultrasonically dispersed uniformly;

[0089] In the third step, 43.58 mg of Se powder was added to the above reaction kettle at room temperature, and then 2 ml of 80% hydrazine hydrate solution was injected and stirred for 30 minutes to mix evenly. The solution was observed to change from green to purple suspension;

[0090] The fourth step was to place the reactor in an electric constant temperature blast drying oven, and heat the temperature from room temperature to 180°C at a rate of 2°C / min and keep the temperature for 24 hours.

[0091] The fifth step is to wait until the reaction system cools down to room temperature naturally, transfer the product in the reactor into a centrifuge tube, centrifuge and wash it alternately with anhydrous ethanol and deionized water for 3 times, then place the product in a vacuum drying oven at 60°C and dry it for 4 hours, take out the product and seal it for storage.

[0092] (2) Preparation of Ni2SeS / PCS

[0093] Step 1: Weigh 40 mg of the NiSe2 / PCS prepared above and spread it evenly in a 1 cm x 4 cm corundum boat;

[0094] Step 2: Place the porcelain boat in the center of the quartz tube in the CVD tube furnace and place 0.2g of sulfur powder at the upwind side of the quartz tube;

[0095] Step 3: Before the reaction starts, a certain amount of N2 gas is introduced and the flow rate is maintained at 0.5 L / min;

[0096] Step 4: Under N2 atmosphere, the temperature was rapidly increased from room temperature to 200°C at a heating rate of 10°C / min, and then slowly increased to 450°C at a heating rate of 2°C / min and kept at this temperature for 1 hour.

[0097] Step 5: Wait until the reaction system cools down to room temperature naturally, and transfer the product in the porcelain boat to a test tube for further characterization and testing.

[0098] Example 3

[0099] Adjust the ratio of NiSe2 / PCS and sulfur powder in the preparation of Ni2SeS / PCS.

[0100] (1) Preparation of NiSe2 / PCS

[0101] First, weigh 120 mg of nickel nitrate hexahydrate and dissolve it in 30 mL of deionized water. Stir at room temperature for 5 minutes. Use a pipette to transfer 20 mL of the solution to a polytetrafluoroethylene reactor.

[0102] In the second step, 20.0 mg of porous carbon spheres were accurately weighed and added to the above reactor, and ultrasonically dispersed uniformly;

[0103] In the third step, 43.58 mg of Se powder was added to the above reaction kettle at room temperature, and then 2 ml of 80% hydrazine hydrate solution was injected and stirred for 30 minutes to mix evenly. The solution was observed to change from green to purple suspension;

[0104] The fourth step was to place the reactor in an electric constant temperature blast drying oven, and heat the temperature from room temperature to 180°C at a rate of 2°C / min and keep the temperature for 24 hours.

[0105] The fifth step is to wait until the reaction system cools down to room temperature naturally, transfer the product in the reactor into a centrifuge tube, centrifuge and wash it alternately with anhydrous ethanol and deionized water for 3 times, then place the product in a vacuum drying oven at 60°C and dry it for 4 hours, take out the product and seal it for storage.

[0106] (2) Preparation of Ni2SeS / PCS

[0107] Step 1: Weigh 40 mg of the NiSe2 / PCS prepared above and spread it evenly in a 1 cm x 4 cm corundum boat;

[0108] Step 2: Place the porcelain boat in the center of the quartz tube in the CVD tube furnace, and place 0.2g, 0.4g, and 0.8g sulfur powder at the upwind side of the quartz tube;

[0109] Step 3: Before the reaction starts, a certain amount of N2 gas is introduced and the flow rate is maintained at 0.5 L / min;

[0110] Step 4: Under N2 atmosphere, the temperature was rapidly increased from room temperature to 200°C at a heating rate of 10°C / min, and then slowly increased to 450°C at a heating rate of 2°C / min and kept at this temperature for 1 hour.

[0111] Step 5: Wait until the reaction system cools down to room temperature naturally, and transfer the product in the porcelain boat to a test tube for further characterization and testing.

[0112] The present invention successfully prepares a binary metal sulfide-carbon-based composite material using a combination of a hydrothermal method and vapor deposition, using nickel salt as a nickel source and selenium powder as a selenium source. This hydrogen evolution reaction catalyst exhibits excellent electrochemical hydrogen evolution properties. The process is simple, the preparation conditions are universal, the product morphology is stable, the purity is high, and the product is easy and simple to handle, making it suitable for medium-scale industrial production.

[0113] The above description of the embodiments is intended to facilitate understanding and application of the present invention by those skilled in the art. It will be apparent to those skilled in the art that various modifications to these embodiments can be readily made and that the general principles described herein can be applied to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the embodiments described herein, and modifications made without departing from the scope of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A hydrogen evolution reaction catalyst, characterized in that: It is a porous carbon sphere composite material modified by Ni2SeS alloy nanorods.

2. The method for preparing the hydrogen evolution reaction catalyst according to claim 1, characterized in that: The following steps are involved: (1) Preparation of NiSe2 / PCS composites by hydrothermal synthesis; (2) Prepare Ni2SeS / PCS composite material by chemical vapor deposition: weigh NiSe2 / PCS and spread it evenly in a corundum porcelain boat, place the porcelain boat in the center of a quartz tube in a CVD tube furnace, and place sulfur powder at the upwind side of the quartz tube, wherein the mass ratio of NiSe2 / PCS to sulfur powder is 1:5-1:20; then introduce N2 gas flow as a protective gas flow, and the flow rate of N2 protective gas flow is 0.5-0.8L / min. Heat the reaction system and keep it warm in two stages, the heating rate in the first stage is 5-10℃ / min, and the heating rate in the second stage is 2-5℃ / min, the temperature is raised to 450-500℃, and the temperature is kept warm for 1-2h; after the reaction is completed, the reaction system is cooled to room temperature, and the product is collected by vacuum drying to obtain Ni2SeS / PCS composite material.

3. The method for preparing a hydrogen evolution reaction catalyst according to claim 2, characterized in that: The preparation method of the NiSe2 / PCS composite material comprises: (1) weighing a nickel salt, dissolving it in a solvent, and adding it to a reaction kettle; (2) Weighing porous carbon spheres and adding them into a reactor, and uniformly dispersing them by ultrasonication; (3) Add Se powder to the reaction kettle, then inject hydrazine hydrate solution and stir; (4) heating the reactor and keeping it warm; (5) Cooling the reaction system to room temperature, centrifuging the product in the reactor, washing it three times with anhydrous ethanol and deionized water, and vacuum drying to obtain a NiSe2 / PCS composite material.

4. The method for preparing a hydrogen evolution reaction catalyst according to claim 3, characterized in that: In the preparation method of the NiSe2 / PCS composite material, the solvent in step (1) is deionized water; and the purity of the nickel salt in step (1) is not less than chemical purity.

5. The method for preparing a hydrogen evolution reaction catalyst according to claim 3, characterized in that: In the preparation method of the NiSe2 / PCS composite material, the concentration of the porous carbon spheres dissolved in deionized water in step (2) is 0.5-1 mg / mL; the mass ratio of the nickel salt in step (1) to the porous carbon spheres in step (2) is (1.5-6):

1.

6. The method for preparing a hydrogen evolution reaction catalyst according to claim 3, characterized in that: In the preparation method of the NiSe2 / PCS composite material, the purity of the Se powder in step (3) is not less than chemical purity; the mass concentration of the hydrazine hydrate solution in step (3) is 60%-80%; the volume of the hydrazine hydrate solution in step (3) is 1-2mL; the mass ratio of the Se powder in step (3) to the nickel salt in step (1) is 2:

1.

7. The method for preparing a hydrogen evolution reaction catalyst according to claim 3, characterized in that: In the preparation method of the NiSe2 / PCS composite material, the heating rate in step (4) is 2-5°C / min; the insulation temperature in step (4) is 180-200°C; and the insulation time in step (4) is 18-24h.

8. The method for preparing a hydrogen evolution reaction catalyst according to claim 3, characterized in that: In the preparation method of the NiSe2 / PCS composite material, the vacuum drying time in step (5) is 4-10 hours; and the vacuum drying temperature in step (5) is 60-70°C.

9. Use of the hydrogen evolution reaction catalyst according to claim 1 in electrocatalytic hydrogen evolution.

Citation Information

Patent Citations

  • Preparing method for carbon cloth load Ni-S-Se nanosheet array

    CN107523845A